Incorporating Artificial Intelligence into Islamic Education: An Epistemological Framework for Knowledge Interconnection in the Age of Industry 5.0 - Akbar Yusgiantara; Baidi Baidi (Lisyabab : Jurnal Studi Islam dan Sosial, 2025)
This research seeks to investigate the conceptual synergy between M. Amin Abdullah’s integrative-interconnective epistemology and the use of artificial intelligence in Islamic education in the context of the Industrial Revolution 5.0. The study used a qualitative library technique to critically analyze original philosophical texts, peer-reviewed journal papers, and policy documents, therefore constructing a theoretical framework that contextualizes AI within Islamic educational principles. The investigation revealed that the majority of current methods for AI integration in education mostly emphasize technical and practical dimensions, neglecting the ethical and epistemological factors crucial to Islamic pedagogy. The results demonstrate that Abdullah's framework offers a thorough basis for integrating technical innovation with the spiritual, ethical, and intellectual aspects of knowledge. This research presents a conceptual paradigm that directs curriculum creation, policy design, and teacher capacity enhancement, guaranteeing that AI implementation upholds the maqashid sharia and the cultural integrity of Islamic institutions. The study offers a unique viewpoint by illustrating that AI may serve as a catalyst for epistemic renewal when aligned with a cohesive Islamic framework. These findings are anticipated to guide next empirical research and facilitate the development of contextually relevant digital transformation initiatives in Islamic education.